The interdisciplinary development of a Feedback Literacy e-Learning Module for undergraduate Healthcare Students. - Davis, Siobhan (My University, 2024)
Central to the supervision and education of all health and social care professional students is the provision and receipt of feedback. Students learn within clinical environments and clinical environments serve as unique learning settings where meaningful feedback is shared between supervisors and students. Feedback is fundamental to facilitating the students learning and is critical to the development of student competence and confidence. 1 In the clinical setting, it is essential for students to actively engage in the feedback process to enhance their sense of agency. To achieve this, students need intentional support in developing their feedback literacy skills, as their active participation is crucial for effective learning.2 Feedback literacy is a topic that has much conceptual literature, however there is a paucity of research examining intervention research, in the how and if feedback literacy can be developed in a student cohort.3 Supporting the development of health and social care students’ feedback literacy is pertinent in order to ensure high-quality learning experiences, the development of professional and clinical competence as well as enhanced reflective skills for future practice.
Working in Partnership and Collaboration, HSCP.